2004
DOI: 10.1086/424527
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Influenza in Children in the Community

Abstract: Influenza causes a substantial burden of illness on outpatient children and their families. Vaccination of children < 3 years old might be beneficial for reducing the direct and indirect costs of influenza in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
188
4
10

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(218 citation statements)
references
References 28 publications
14
188
4
10
Order By: Relevance
“…The symptoms were least accurate among children aged less than one year. This finding is in accordance with the clinical experience of diagnosis of respiratory infections among infants, although the burden of influenza is greater in this age group [23,24] . 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 9 In the present study, influenza infection was identified in 18% of children aged 6 months to 14 years who were hospitalized with fever and/or respiratory symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…The symptoms were least accurate among children aged less than one year. This finding is in accordance with the clinical experience of diagnosis of respiratory infections among infants, although the burden of influenza is greater in this age group [23,24] . 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 9 In the present study, influenza infection was identified in 18% of children aged 6 months to 14 years who were hospitalized with fever and/or respiratory symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…Although estimated rates may be difficult to compare because of differences in study design, populations studied, seasons included, and geography, rate ratios between age groups should be similar. Here our findings are consistent with those from other studies12, 14, 15, 16, 17, 23: Young children bear the brunt of the outpatient influenza burden. Finally, although our study included >7 million persons, a larger population than other US studies, all data were from integrated health systems.…”
Section: Discussionsupporting
confidence: 93%
“…By contrast, influenza‐associated outpatient visits are plentiful, so rates of laboratory‐confirmed visits should be easier to document. However, relatively few studies have made population‐based estimates of influenza‐confirmed outpatient visit rates 12, 13, 14, 15, 16, 17. Most have focused on children, typically in a single site 12, 14, 15, 16, 17.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted in North America, Europe, and Asia have documented that children have particularly high rates of morbidity and influenza‐related complications, particularly those aged <2 years 1, 2, 3. Although effectiveness varies by season through the interaction of viral and host factors, annual influenza vaccination remains the most effective method for preventing seasonal influenza and related complications 4, 5, 6, 7.…”
Section: Introductionmentioning
confidence: 99%